Launching a unique program on biosciences innovation in eastern Africa - Leta, S. (International Livestock Research Institute, 2011)
Seyoum Leta (Bio-Innovate, Program Manager) said that the launching held on 16 March 2011 is the official launch date for Bio-Innovate, a unique regional agricultural research initiative that is Africa based, Africa led and focuses on innovations for farmers.